XIX Brazilian Colloquium on Orbital Dynamics (2018): A solid path to the 21st century - De Melo, C. F.; Prado, A. F.B.A.; Macau, E. E.N.; Winter, O. C. [UNESP] (My University, 2019)
The Brazilian Colloquium on Orbital Dynamics (CBDO) is a scientific meeting that takes place every two years since 1982. Its main goal is to bring together researchers, professors, undergraduate and post graduate students who develop works on pure and applied Celestial Mechanics in the same lectures and discussions atmosphere, and thus to drive collaboration between these areas. The XIX CBDO 2018 took place at the Test and Integration Laboratory (LIT) of the National Institute for Space Research (INPE), in São José dos Campos (SP), Brazil, between December 03 - 07, 2018, and more than 230 attendant from South and North America, Europe and Asia presented works of which 31 were selected for publication in this volume of the Journal of Physics: Conference Series. The highlight of this issue is the consolidation of the research groups on Celestial Mechanics in several Brazilian universities.